Pupil behaviour on school buses and potential risk factors for injury: an observational study - Sharon Goldman; Kobi Peleg
OBJECTIVE: To observe pupil behaviour on school buses in Israel and identify hazards as a basis for improving school bus safety. METHODS: Data on student, bus driver and chaperone behaviours and on hazards associated with school buses, bus loading zones and bus stops were collected during an observational study conducted on school buses in rural communities in Israel. This report focuses on observations of student behaviour during school bus rides. Future reports will discuss the other findings. Student behaviours were assessed by means of c² tests and logistic regression models. FINDINGS: Observations were made on 362 rides on 125 buses on which 11 000 pupils travelled to and from school. Seatbelt use among the pupils was limited: on 23% of the rides all pupils fastened seatbelts, while on 42% none did. Seatbelt use was more frequent among primary school pupils than among older pupils. Pupil behaviours, such as rowdiness, noisiness, conflicts between pupils and not remaining seated were observed. These and other unsafe behaviours were more frequent on afternoon bus rides (odds ratio, OR: 3.2, 95% confidence interval, CI: 2.1-5.3), on routes with 5+ bus stops (OR: 4.1; 95% CI: 2.5-6.5) and on rides with primary school pupils (OR: 1.8; 95% CI: 1.2-2.9). CONCLUSION: Without enforcement, government regulations and seatbelt availability on school buses are not enough to ensure seatbelt usage among pupils. Bus drivers cannot be expected to enforce seatbelt use and deal with pupil misconduct while also driving safely. Innovative strategies for improving pupil behaviour on school buses are needed to increase pupil safety.